Introduction to the Post-Human Genome Project era, a target for interactions between polygenic and/or multiphenotypical components in cancer control in South America - José Iscovich
Epidemiological studies have suggested that the propensity to develop malignancy involves a complex mix of genetic and environmental determinants, however both older and innovative techniques display unresolved questions regarding etiology. Current barriers to achieving the potential benefit from this understanding are: 1) incomplete background on the various environmental and genetic factors involved in the carcinogenesis mechanism; 2) difficulties in accurately differentiating specific molecular subtypes and measuring the effective cellular exposure dose; and 3) difficulties in determining the multifactorial interaction between genetic and environmental factors. To extrapolate Human Genome Project research findings to the Post-Human Genome Project era, South America provides a large population and large-pedigree families, thus including genetically heterogeneous and less heterogeneous groups. An initial strategy might be to trace high risk populations and the respective exposures to which they are susceptible, such as: 1) migration, identifying rural migrant populations; 2) inherent susceptibility, studying "long term homogeneous populations" or large families living in similar rural environments; and 3) dissection of gene-environmental interaction.